Analysis of Nursing Dissertations and Theses on Mental Health, Brazil, 1979-2007 Análisis de las disertaciones y tesis de enfermería sobre salud mental, Brasil, 1979-2007 Análise das dissertações e teses de enfermagem sobre saúde mental, Brasil, 1979-2007 - Kely Vanessa Leite Gomes da Silva; Arisa Nara Saldanha de Almeida; Ana Ruth Macedo Monteiro; Lia Carneiro Silveira; Ana Virgínia de Melo Fialho; Thereza Maria Magalhães Moreira (Universidade de São Paulo, 2010)
This bibliographic study analyzes scientific texts published in the CEPEn database in the mental health field (1979-2007). A total of 280 abstracts were investigated, of which 208 were Master's theses. The individuals investigated in these studies were professionals (57), patients (50), and professors and/or students (18). Among the themes addressed between 2000 and 2007 were the following: Nursing Care in Mental Health (40), Perception in Mental Health (37); and Transversality in Mental Health Care (27). This study provided an overview of the scientific research produced in the mental health field in Brazilian nursing graduate programs. We expect this study to elicit reflections concerning mental health care practice and enable new approaches for nursing promoting health and the prevention of diseases in order to enable patients to recover their citizenship, autonomy and quality of life. Se trata de un estudio bibliográfico, con el objetivo de analizar los textos científicos divulgados en la base de datos CEPEn en el área de salud mental (1979-2007). El total de resúmenes estudiados fueron 280, de los cuales 208 eran disertaciones de maestría. Los sujetos que se destacaron fueron los profesionales (57) y pacientes (50). Entre las temáticas abordadas se evidenciaron (2000-2007): el Cuidado de Enfermería en Salud Mental (40) y la Percepción en Salud Mental (37). Este trabajo posibilitó obtener una visión panorámica sobre la producción científica en salud mental en los cursos de Posgraduación en Enfermería en Brasil. Esperamos que el estudio incentive la reflexión sobre las prácticas de cuidado en salud mental y posibilite nuevos abordajes en enfermería con el objetivo de promover la salud y prevenir daños, de forma a favorecer la ciudadanía, la autonomía y la calidad de vida de los sujetos envueltos. Trata-se de estudo bibliográfico, com o objetivo de analisar os textos científicos, divulgados na base de dados CEPEn, na área de saúde mental (1979-2007). O total de resumos estudados foi 280, dos quais 208 constituíam-se de dissertações de mestrado. Os sujeitos que se destacaram foram os profissionais (57) e pacientes (50). Dentre as temáticas abordadas evidenciaram-se (2000-2007): o cuidado de enfermagem em saúde mental (40) e a percepção em saúde mental (37). Este trabalho possibilitou visualização panorâmica acerca da produção científica em saúde mental nos cursos de pós-graduação em enfermagem, no Brasil. Espera-se, aqui, que o estudo suscite reflexões acerca das práticas de cuidado em saúde mental e possibilite novas abordagens em enfermagem, com vistas à promoção da saúde e prevenção de agravos que favoreçam a cidadania, autonomia e qualidade de vida dos sujeitos envolvidos.